(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Determination of quality of production of the same kind is performed in its predominant part by means of sampling test. This also applies to manufacture of particleboards (PBs). Sttistical methods allow assessing and comparing the quality of products. To assess and compare the quality of individual manufacturers with respect to standard requirements, an interval estimate of the arithmetic mean value of indices has been used, and to compare the quality between different manufacturers, a test of hypothesis with respect to mean values of two samples has been used. After performed tests of laminated particleboards (LPBs) of different manufacturers, statistically significant differences in the quality level between individual manufacturers have been established. The aim of the investigation is approval of methods for application of statistical methods when selecting a manufacturer / supplier of PBs according to objective criteria related to pro-duction quality.